Field evaluation of a rapid antigen test (Panbio™ COVID-19 Ag Rapid Test Device) for COVID-19 diagnosis in primary healthcare centres. (March 2021) - Albert, Eliseo; Torres, Ignacio; Bueno, Felipe; Huntley, Dixie; Molla, Estefanía; Fernández-Fuentes, Miguel Ángel; Martínez, Mireia; Poujois, Sandrine; Forqué, Lorena; Valdivia, Arantxa; Solano de la Asunción, Carlos; Ferrer, Josep; et al.
Abstract: Objectives: To our knowledge no previous study has assessed the performance of a rapid antigen diagnostic immunoassay (RAD) conducted at the point of care (POC). We evaluated the Panbio™ COVID-19 Ag Rapid Test Device for diagnosis of coronavirus 2019 disease (COVID-19) in symptomatic patients ( n  = 412) attending primary healthcare centres. Methods: RAD was performed immediately after sampling following the manufacturer's instructions (reading at 15 min). RT-PCRs were carried out within 24 h of specimen collection. Samples displaying discordant results were processed for culture in Vero E6 cells. Presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in cell cultures was confirmed by RT-PCR. Results: Out of 412 patients, 43 (10.4%) tested positive by RT-PCR and RAD, and 358 (86.9%) tested negative by both methods; discordant results (RT-PCR+/RAD–) were obtained in 11 patients (2.7%). Overall specificity and sensitivity of rapid antigen detection (RAD) was 100% (95%CI 98.7–100%) and 79.6% (95%CI 67.0–88.8%), respectively, taking RT-PCR as the reference. Overall RAD negative predictive value for an estimated prevalence of 5% and 10% was 99% (95%CI 97.4–99.6%) and 97.9% (95%CI 95.9–98.9), respectively. SARS-CoV-2 could not be cultured from specimens yielding RT-PCR+/RAD– results ( n  = 11). Conclusion: The Panbio™ COVID-19 Ag Rapid Test Device performed well as a POC test for early diagnosis of COVID-19 in primary healthcare centres. More crucially, the data suggested that patients with RT-PCR-proven COVID-19 testing negative by RAD are unlikely to be infectious.